I am just curious as to how this fits in. If momentum P=mv, and kinetic energy KE=1/2mv^2, how would one combine, derive, switch and swap (whatever the process is called), these two equations to end up with the formula m=P^2/2KE. It seems like a no-brainer, but I can't seem to make sense of the algebra.(adsbygoogle = window.adsbygoogle || []).push({});

Thanks,

JHCreighton

**Physics Forums - The Fusion of Science and Community**

# M=P^2/2KE: How is this derived?

Have something to add?

- Similar discussions for: M=P^2/2KE: How is this derived?

Loading...

**Physics Forums - The Fusion of Science and Community**